Ready-to-use single tube quadruplex PCR for differential identification of mutton, chicken, pork and beef in processed meat samples. Issue 10 (3rd October 2019) - Balakrishna, Konduru; Sreerohini, Sagi; Parida, Manmohan
ABSTRACT: A reliable and sensitive identification method is required to tackle food adulteration mainly in meat production. We developed a dry reagent based ready-to-use single tube quadruplex PCR assay for accurate identification of chicken, mutton, beef and pork. The assay was found to be specific and reproducible. Thermo-stability studies of lyophilized PCR master mix were conducted at different temperature and time intervals, which revealed significant stability for 75 days at 4°C and for 60 days at 25°C. The developed assay was shown to be sensitive down to 16 pg DNA per reaction and the detection limit was found to be 0.01% (w/w) of each species. Furthermore, this method has been applied to the analysis of 68 commercial meat products and the results indicated that nine samples contained non-declared meat components. This dry reagent-based quadruplex PCR assay can be utilized to monitor various processed food products and also to maintain quality control in food industries mainly in the resource-limited settings. GRAPHICAL ABSTRACT: